THERMAL PERFORMANCE OF PARABOLIC TROUGH SOLAR COLLECTOR - Karima E Amori; Randa R Sari (Iraqi Journal for Mechanical and Materials Engineering, 2018)
This work presents design, instrumented and test of a parabolic trough solar collector under Baghdad climate conditions (of latitude 33.33o N, of longitude 44.4o E). The parabolic trough solar collector consists of: a mirror matrix or tapes which work as reflective surface of (2m *1m), absorber copper tube (receiver), two axis tracking system. Water is used as a heat transfer medium. The setup is tested within clear days from June, to September 2017. The collector heat gain, efficacy and temperature of absorber were presented for absorber five different circulating mass flow rates of (0.15, 0.2, 0.3, 0.4, 0.5) 1pm. The results show that the maximum thermal efficiency of the parabolic trough solar collector is 80.26%. The maximum outlet temperature of the absorber tube reaches 81 oC at the noon when water flows at (0.15) 1pm. The maximum obtained heat gain is (1619W) for (0.5) 1pm flow rate of water.